Biofilm in wounds: nurses' knowledge in evaluation and treatment (Research, Society and Development, 2021)
Objective: To identify nurses' knowledge about biofilm in complex wounds. Method: Descriptive and cross-sectional study, carried out in five inpatient units of adult patients in a public teaching hospital in the state of Mato Grosso do Sul. For data collection, a semi-structured, self-administered instrument consisting of 26 questions was used. This study was approved by the Human Research Ethics Committee of the Federal University of Mato Grosso do Sul under opinion number 3.727.518. Results: 52 professionals participated in the research, with a mean age of 37.63 years and a predominance of females. Most had experience in the area and worked in the urgency and emergency unit, in the day shift and had specialization as their highest level of training. As for receiving training about biofilm, most reported not having received it. The questions with the highest percentage of incorrect answers were related to diagnosis and treatment. Conclusion: Participants had limitations in knowledge about biofilm in complex wounds, which can influence clinical practice. It is believed that the lack of activities aimed at teaching and learning in the institution has contributed to these results.